Lessons Learned Designing and Using an Online Discussion Forum for Care Coordinators in Primary Care. (November 2016) - Ferrante, Jeanne M.; Friedman, Asia; Shaw, Eric K.; Howard, Jenna; Cohen, Deborah J.; Shahidi, Laleh
While an increasing number of researchers are using online discussion forums for qualitative research, few authors have documented their experiences and lessons learned to demonstrate this method's viability and validity in health services research. We comprehensively describe our experiences, from start to finish, of designing and using an asynchronous online discussion forum for collecting and analyzing information elicited from care coordinators in Patient-Centered Medical Homes across the United States. Our lessons learned from each phase, including planning, designing, implementing, using, and ending this private online discussion forum, provide some recommendations for other health services researchers considering this method. An asynchronous online discussion forum is a feasible, efficient, and effective method to conduct a qualitative study, particularly when subjects are health professionals.